Methods for the substitution of common saponification systems for the solvent extraction of REEs. Issue 2 (4th March 2017) - Liu, Yang; Sohn, Seong Ho; Lee, Man Seung
Abstract: In order to develop efficient and environmentally friendly systems for the substitution of common saponification systems for the solvent extraction of rare earths elements (REEs), the conventional mixtures of acid/base extractants and ionic liquids containing acid/base components were compared. All of these systems performed better extractability and selectivity than individual extractants. The extraction mechanisms of different systems were analyzed based on the physico-chemical properties of extractants and the interaction between components. Although the mechanisms of these systems are different, they all provide the possibility to avoid numerous saponification procedures and decrease the saponification wastewater in the REEs separation industry. The study contributes to further understanding the mechanisms and applications of novel REEs extraction systems which can replace the saponification systems.